Leadership styles and their role in enhancing the intellectual capital Field research in the Ministry of Foreign - الطائي, علي حسون; الزبيدي, لمى قيس (Journal of Economics and Administrative Sciences, 2017)
This study has taken into consideration two vital variables (leadership, leadership styles and intellectual capital). The research aim through the relations between the leadership styles and intellectual capital, to building conceptual frame for the variables of study and exploring the nature of correlation relations between these variables and their effects in enhancing intellectual capital.      The research was conducted at the Ministry of foreign in Iraq, and included a sample of leaders and subordinates amounted to (186), has been using the questionnaire as a key tool to collect data on the sample.      For the dealing with collected data and reached the results, the research tried to test some hypotheses related to the correlation and regression among the variables. For the purpose of dealing with and processing data and information, the researcher has used many statistical techniques, such as (mean, standard deviation, percentages, spearman rank, and simple regression).      The reseach found a set of conclusions such as the effect of varying patterns of leadership in building and strengthening intellectual capital, and the varying answers of the sample of leaders and subordinates about the variables of the study.      According to the conclusions that have been reached, it was a set of recommendations introduced, hoping to take advantage of them by the ministry researched such as the necessity for the ministry researched the development unit within its organizational structure called (unit intellectual capital), working to enrich people’s information (leaders and subordinates) about the importance of intellectual capital for the ministry, and his conducting well as a whole or through its components studied in this research, and the diagnosis of individuals who have these abilities and skills.